2016
DOI: 10.1024/1422-4917/a000450
|View full text |Cite
|
Sign up to set email alerts
|

Basic numerical processing, calculation, and working memory in children with dyscalculia and/or ADHD symptoms

Abstract: DD and AS appear to be related to largely distinct patterns of cognitive deficits, which are present in combination in children with DD+AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 53 publications
3
30
0
1
Order By: Relevance
“…This suggests that these children continue to recruit WM resources when performing arithmetic operations in the later grades of primary school while their typically developing peers have already automatized these operations. These results fit in with recent literature on WM and MLD (e.g., Attout et al, 2014;Kuhn et al, 2016;Maehler & Schuchardt, 2016;Szűcs et al, 2013), which proposed a WM-centered approach for explaining mathematical learning difficulties. The present study showed that this seems to hold true for children in later stages of primary school as well.…”
Section: Working Memory and Number Sense In Children With Mathematical Difficulties: Functionally Different From Typical Development?supporting
confidence: 91%
“…This suggests that these children continue to recruit WM resources when performing arithmetic operations in the later grades of primary school while their typically developing peers have already automatized these operations. These results fit in with recent literature on WM and MLD (e.g., Attout et al, 2014;Kuhn et al, 2016;Maehler & Schuchardt, 2016;Szűcs et al, 2013), which proposed a WM-centered approach for explaining mathematical learning difficulties. The present study showed that this seems to hold true for children in later stages of primary school as well.…”
Section: Working Memory and Number Sense In Children With Mathematical Difficulties: Functionally Different From Typical Development?supporting
confidence: 91%
“…Studies included in this review assessed intelligence using different tests, such as Raven’s Standard Progressive Matrices (RSPM) [ 44 , 56 , 57 , 60 ], Raven’s Colored Progressive Matrices (CPM) [ 59 , 70 , 71 , 74 , 76 , 77 ], Cultural Fair Intelligence test (CFT) [ 72 ], reduced versions of different editions of the Wechsler Intelligence Scale for Children (WISC-R- [ 58 ]; WISC III- [ 47 , 53 , 61 , 68 , 69 , 76 , 77 , 78 ]; WISC IV [ 73 , 79 ]), the Wechsler Abbreviated Scale of Intelligence (WASI) [ 31 , 54 , 64 , 65 ], the Stanford–Binet Intelligence Scales [ 75 ], the Primary Mental Abilities (PMA) [ 66 , 67 ]; the Intelligence and Developmental Scale (IDS) [ 80 ], and the Peabody Picture–Vocabulary test (PPVT) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…They likewise fail to comprehend this principle despite otherwise healthy mathematical development ( Kamawar et al, 2010 ). Kuhn et al (2016) infer that DD essentially reflects a deficit of specific precursor abilities that healthy infants are endowed with even before learning arithmetic or calculation (i.e., estimation, enumeration, and transcoding). Longitudinal studies accordingly show that basic quantity-based abilities including number naming, counting, and estimation are stable predictors of arithmetic proficiency during the transition from preschool to kindergarten ( VanDerHeyden et al, 2006 ), elementary school ( Methe et al, 2008 ; Lembke and Foegen, 2009 ), and high school ( Siegler et al, 2012 ), independent of general intelligence levels ( Locuniak and Jordan, 2008 ).…”
Section: Developmental Dyscalculiamentioning
confidence: 99%